Ochrona praw podstawowych w internetowym procesie przetwarzania danych osobowych w Unii Europejskiej - Prus, Łukasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
In nowadays protection of fundamental rights takes on new importance together with the development of technologies in the field of Internet. In this legal space, there is often a conflict between the fundamental rights of the data controller, person whose these data concern and all of the users of Internet. Thus the conflict of rights in horizontal relations between equivalent entities. The article tries to answer the question whether parties of this legal relationship are allowed to effectively seek protection based on the rules of administrative law. The article analyzes three situations concerning the protection of fundamental rights: 1) publication of personal data on the website, 2) personal data as a result of the search, 3) IP address as a personal data.
Keywords: web search engine; data protection in Internet; IP address; new technologies; fundamental rights